The Influence of Organizational Culture and Organizational Climate, on Employee Performance and Job Satisfaction as Mediation Variables (Study at the Public Works Office (PU) of Ternate City) - Rathi Nuryani Achmad*; Marwan Marwan; Adnan Rajak (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the effect of organizational culture and organizational climate on employee performance through job satisfaction. This research is a quantitative research. The population in this study were Ternate City Public Works (PU) employees. The number of research samples is 91 respondents. The data analysis technique used in this study was SEM analysis using Smart Partial Least Square (PLS) version 4 as a statistical test tool.The results of this study indicate that: (1) Organizational Culture has a positive and significant effect on job satisfaction; (2) organizational climate has a positive and significant effect on job satisfaction; (3) Organizational culture has a positive and significant effect on performance (4) organizational climate has a positive and significant effect on performance; (5) satisfaction has a positive and significant effect on performance (6) job satisfaction is able to mediate the influence of organizational culture on performance; (7) Job satisfaction is able to mediate the effect of organizational climate on performance.